Julian Mortimer: A Brave Boy's Struggle for Home and Fortune - Castlemon, Harry, 1842-1915; Hacket, Owen; Stockton, Russell (Salt Lake City, UT : Project Gutenberg, 2016)
"Julian Mortimer: A Brave Boy's Struggle for Home and Fortune" by Harry Castlemon is a novel written in the late 19th century. The story follows the adventures of Julian Mortimer, a young boy navigating life in the American frontier, filled with danger, wild landscapes, and the quest for belonging. As the main character, Julian's journey leads him through perils that test his courage and resilience, all while seeking his true identity and a home he feels connected to. At the start of the narrative, Julian and a seasoned trapper named Silas Roper prepare to select a campsite for their wagon train while evading a lurking Indian threat. This setting quickly evolves into a tense atmosphere when Julian learns of an impending danger not just from the Indians, but also from two men plotting against him. The stakes rise dramatically as he discovers he is being sought after by two factions$1 (Bone desiring him dead and the other willing to pay a fortune for him alive. This compelling beginning introduces readers to Julian's struggles, foreshadowing the trials he will face in his hopes for safety and a sense of belonging. (This is an automatically generated summary.)s
Julian Mortimer, or, a brave boy's struggle for home and fortune / by Harry Castlemon -- An idea and a fortune / by Owen Hackett -- The Grantham diamonds / by Russell Stockton.
Release date is 2016-04-12
E-text prepared by Giovanni Fini, Melissa McDaniel, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Conduct of life -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Diligence -- Juvenile fiction; Success -- Juvenile fiction; Outdoor life -- Juvenile fiction; Courage -- Juvenile fiction; Trappers -- Juvenile fiction; Wealth -- Juvenile fiction